Elimination of bacterial contaminations by treatment of water with boron-doped diamond electrodes - Schorr, Bastian; Ghanem, Hanadi; Rosiwal, Stefan; Geißdörfer, Walter; Burkovski, Andreas (World Journal of Microbiology & Biotechnology, 2019)
Boron-doped diamond electrodes can be used to generate reactive oxygen species directly at the electrode’s surface. This property was used in this study for in-situ electrochemical oxidation to eliminate different bacteria, i.e. Escherichia coli, Pseudomonas fluorescens and Pseudomonas aeruginosa, as well as Bacillus subtilis spores from water samples. Application of low voltages in the rage from 4 to 10 V and short incubation times in the range of minutes allowed a complete disinfection of water contaminated with enterobacteria and freshwater microbes including nosocomial pathogens as well as a significant reduction of spores. A pilot reactor was constructed, which allowed to decrease microbial contamination of sewage plant effluent drastically.
Keywords: Reactive oxygen species; Sewage treatment plant; Drinking water; Potable water; Water purification